The Effect of the Teach-Back Method on Knowledge, Performance, Readmission, and Quality of Life in Heart Failure Patients - Ali Rahmani; Amir Vahedian-Azimi; Masoud Sirati-Nir; Reza Norouzadeh; Hamid Rozdar; Amirhossein Sahebkar (Cardiology Research and Practice)
Background. Among chronic diseases, heart failure has always been a serious challenge imposing high costs on health systems and societies. Therefore, nurses should adopt new educational strategies to improve self-care behaviors and reduce the readmissions in heart failure patients. This study aimed to determine the effect of the teach-back method on knowledge, performance, readmission, and quality of life in these patients. Methods. This clinical trial was conducted in patients with heart failure (n = 70) hospitalized in the internal wards of the Baqiyatallah al-Azam Medical Center in Tehran (2019). Routine discharge educations were provided in control patients. Self-care topics were taught to the intervention groups by the teach-back method. A cardiac self-care questionnaire was used to assess the knowledge and practice of patients immediately after intervention and three months after patient discharge. Also, SF-36 was presented to each patient. Readmission(s) and quality of life were followed up by telephone interviews three months after patient discharge. Repeated measures analysis of variance and related post-hoc tests were performed for within-group comparisons before, immediately after, and 3 months after teach-back education. Wilks’ lambda multivariate tests were conducted for simultaneous comparison of quality of life subscales between intervention and control groups. Also, logistic regressions were after controlling for baseline measures and confounders. Results. Findings showed significant improvement in the patients’ knowledge and performance immediately after teach-back education, though this effect was slow in the long term after discharge. Also, the frequency of readmissions decreased and the quality of life (except physical function) increased in the patients through teach-back education. By controlling for the pretest effect, the posttest scores for the relevant components of the quality of life suggested improvement in both intervention and control patients. This improvement in the quality of life was confirmed by controlling for baseline measurements using binary logistic regression analysis. Conclusion. Teach-back education improved patients’ knowledge and performance, readmission frequency, and quality of life.